An Unwanted Association: The Threat to Papaya Crops by a Novel Potexvirus in Northwest Argentina - Cabrera Mederos, Dariel; Debat, Humberto Julio; Torres, Carolina; Portal, Orelvis; Jaramillo Zapata, Margarita; Trucco, Veronica Milagros; Flores, Ceferino Rene; Ortiz, Claudio Manuel; Badaracco, Alejandra; Acuña, Luis Eduardo; Nome Docampo, Claudia; Quito-Avila, Diego; et al. (MDPI, 2022)
An emerging virus isolated from papaya (Carica papaya) crops in northwestern (NW) Argentina was sequenced and characterized using next-generation sequencing. The resulting genome is 6667-nt long and encodes five open reading frames in an arrangement typical of other potexviruses. This virus appears to be a novel member within the genus Potexvirus. Blast analysis of RNA-dependent RNA polymerase (RdRp) and coat protein (CP) genes showed the highest amino acid sequence identity (67% and 71%, respectively) with pitaya virus X. Based on nucleotide sequence similarity and phylogenetic analysis, the name papaya virus X is proposed for this newly characterized potexvirus that was mechanically transmitted to papaya plants causing chlorotic patches and severe mosaic symptoms. Papaya virus X (PapVX) was found only in the NW region of Argentina. This prevalence could be associated with a recent emergence or adaptation of this virus to papaya in NW Argentina.